The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1097/gme.0000000000000905
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation effects on menopausal vasomotor symptoms

Abstract: Our results suggest that the tDCS technique showed small trends on postmenopausal vasomotor symptoms, justifying searches for more effective methods by which tDCS could reduce hot flashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Among the TES studies, eight of them used CES (49-56), seven applied tDCS (57)(58)(59)(60)(61)(62)(63), and one examined tACS (64). No study was identified to have examined the effectiveness of tRNS in insomnia.…”
Section: Resultsmentioning
confidence: 99%
“…Among the TES studies, eight of them used CES (49-56), seven applied tDCS (57)(58)(59)(60)(61)(62)(63), and one examined tACS (64). No study was identified to have examined the effectiveness of tRNS in insomnia.…”
Section: Resultsmentioning
confidence: 99%